"Reactive" response evaluation of primary human astrocytes after methylmercury exposure. Issue 1 (3rd October 2013) - Malfa, Giuseppe A.; Tomasello, Barbara; Sinatra, Fulvia; Villaggio, Giusy; Amenta, Francesco; Avola, Roberto; Renis, Marcella
<x xml:space="preserve">Abstract</x> Astrocytes are actively involved in brain development, in mature CNS regulation, and in brain plasticity. They play a critical role in response to cerebral injuries and toxicants through a reaction known as "reactive gliosis, " which is characterized by specific structural and functional features. A large amount of literature highlights the central role of astrocytes in mediating methylmercury (MeHg) neurotoxicity. In fact, mercury is the major neurotoxic pollutant that continues to arouse interest in research because of the severe risk it poses to human health. In this article, we focus on the action of MeHg on human astrocyte (HA) reactivity. We clearly demonstrate that MeHg induces a state of cellular suffering by promoting delayed and atypical astrocyte reactivity mediated by impairment of the proliferative and trophic component of the astrocyte together with an inflammatory state. This condition is generated by negative modulation of the major proteins of the filamentous network, which is manifested by the destabilization of astrocytic cytoarchitecture. Our data confirms the toxic effects of MeHg on HA reactivity and allows us to hypothesize that the establishment of this state of suffering and the delayed onset of a typical astrocytic reactivity compromise the main protective function of HA. © 2013 Wiley Periodicals, Inc.